EVALUASI MASTERPLAN POLITEKNIK NEGERI AMBON - Margie Civitaria Siahay; Pieter Lourens Frans; Marios Peilouw; Delvia Rimesye Apalem (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Ambon State Polytechnic is located in Ambon city, covering an area of 4.31 hectares. Due to its progress, Ambon State Polytechnic underwent modifications throughout a specific timeframe, necessitating a review. This research identified issues pertaining to underutilized and suboptimal physical spaces that fail to adequately address present requirements. This space encompasses areas for open recreation, lecture halls (classrooms), and parking facilities. The purpose of open space is to address the insufficient social interaction among academics, the inadequate lecture halls that fail to fulfill student requirements, and the insufficient parking spots that do not meet the demand for parking. The findings of this study indicated that Ambon State Polytechnic has 6,039 m2 of land that can still be utilized more effectively in the educational sector, as per the regional legislation, albeit with certain limitations. Ambon State Polytechnic academic community requires a total of 721.8 m2 of Parking Space Requirements. Additionally, the distribution of classroom space across existing departments does not adhere to uniform norms and rules. Utilizing the logic model approach for evaluation, it is evident that the current masterplan is inadequate in addressing present requirements. Consequently, a new plan is imperative to meet the current demands of the academic community.